PERWUJUDAN NILAI KESETIAAN DAN KEHORMATAN BUSHIDOO DALAM NOVEL â47 RONINâ KARYA JOHN ALLYN - , NURMA SARASWATI GUMELAR; , Santi Andayani, S.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The novel entitled "47 Ronin" is a novel by John Allyn was first published in 1970.This novel tells the story of revenge carried out by 47 Ronin to a royal official named Kira, since Kira had killed their master. Ronin is the term given to the samurai who have not have a master. This story happened during the reign of the Tokugawa Shogunate. This story is recognized as one of the best legends in the history of the Japanese samurai. This novel is very accentuate the value of bushido loyalty and honor. Bushido is a system of ethics or warrior moral rules that apply to the Japan samurai in XII-XIX century. One of the rules of bushido is, if a samurai lost fight then he should commit suicide by cutting the stomach (seppuku).In this novel the samurai chose to commit seppuku to preserve his honor than to die at the hands of the enemy. The purpose of this thesis is to investigate the embodiment of the values of bushidosâhonor and loyalty in the novel "47 Ronin". The final task is prepared using the literature by searchingthe sources related to the theme and rewrite it descriptively. From the investigation results on the content of the novel is known that the samurai still adhere to the values of loyalty and honor even though his master had died. One ofthe loyalty and honor is shown through the steps of revenge carried out by 47 ronin to someone who had killed their master Asano. In addition, the novel is also told about the debate between Edo society at that timeabout the fate of the 47 Ronin after revenge. However, the greatness story behind this novel turns the novel also received criticism. One of the famous Japanese writer, Yamamoto Tsunetomo, judging that the story of the samurai (ronin 47) in this novel did not show the values of bushido in the story.